Numerical and Experimental Investigation of Wrinkling Pattern for Aerospace Laminated Membrane Structures - Yihong Hong; Wenjuan Yao; Yan Xu (International Journal of Aerospace Engineering)
Al-polymer laminated membranes are widely used in large aerospace structures. When the laminated membranes are pressurized, wrinkles emerge, which have an important effect on the performance of the structures during operation. This paper describes the numerical simulation and experimental investigation of wrinkles in laminated membranes. The nonlinear postbuckling analysis method, based on laminated thin-shell elements, was used to simulate the onset, growth, and final configuration of wrinkles when laminated membranes are subjected to external loads. The simulations are conducted with the ANSYS finite element package. Changing regularities of number, wavelength, and range for the wrinkles during the onset and growth processes are investigated. The wrinkles of laminated membranes with different design parameters such as material selection, ply number, ply angle, and ply mode are predicted. Devices that can be used to clamp and load laminated membranes in several load cases were designed and developed. A 3D photogrammetry system was constructed to characterize wrinkling patterns of laminated membranes subjected to shear displacement loads. By comparing the results of numerical analysis and experimental results, the accuracy of the numerical analysis method was verified. This study work is expected to inform wrinkling simulation and shape control of aerospace laminated membrane structures.